2012
DOI: 10.5194/acp-12-11261-2012
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of MODIS cloud microphysical properties with in-situ measurements over the Southeast Pacific

Abstract: Abstract. Utilizing the unique characteristics of the cloud over the Southeast Pacific (SEP) off the coast of Chile during the VOCALS field campaign, we compared satellite remote sensing of cloud microphysical properties against insitu data from multi-aircraft observations, and studied the extent to which these retrieved properties are sufficiently constrained and consistent to reliably quantify the influence of aerosol loading on cloud droplet sizes. After constraining the spatial-temporal coincidence between… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
94
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(109 citation statements)
references
References 23 publications
10
94
1
Order By: Relevance
“…To avoid significant distortion of r e by coalescence, we avoided heavily precipitating clouds at their tops (r e 0> 18 μm). MODIS r e is larger than aircraft in situ measurements by 10-15% (34)(35)(36). This is probably not a problem for retrieved r e based on the VIIRS Imager (30), because it is lower by a similar amount with respect to MODIS r e .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid significant distortion of r e by coalescence, we avoided heavily precipitating clouds at their tops (r e 0> 18 μm). MODIS r e is larger than aircraft in situ measurements by 10-15% (34)(35)(36). This is probably not a problem for retrieved r e based on the VIIRS Imager (30), because it is lower by a similar amount with respect to MODIS r e .…”
Section: Discussionmentioning
confidence: 99%
“…The observed 26% underestimate in CCN could have been caused by a 10% systematic overestimate in the retrieved r e . This is quite probable, because MODIS-retrieved r e was found to be larger by 10-15% than aircraft in situ measurements (34)(35)(36). An underestimate of satellite-versus surface-measured CCN can be also caused by a systematic decrease of CCN number concentration (N CCN ) between the surface and cloud base heights.…”
Section: [4]mentioning
confidence: 99%
“…(1), the true droplet number concentration is a product of N and k when a gamma distribution of the droplets is considered. Results of deviations from this hypothesis have been investigated through comparison with the in situ observations (Painemal and Zuidema, 2011;Min et al, 2012). The MODIS CDNC values (derived with f ad = 0.8) are quite close to in situ observations for stratocumulus over the Chile-Peru coast.…”
Section: Modis/aquamentioning
confidence: 92%
“…Saide et al (2012b) argued that WRF-Chem simulates marine cloud-aerosol interactions at a level sufficient for applications in forecasting weather and air quality and studying aerosol climate forcing and may do so with the reliability required for policy analysis. Both studies emphasize the importance of reproducing gradients of aerosol and cloud droplet concentrations that typify the SEP. Saide et al (2012b), on the basis of the remarkably robust correspondence of satellite-derived cloud droplet concentrations to in situ VOCALS data (Painemal and Zuidema 2011;King et al 2013;Min et al 2012), are assimilating satellite-observed cloud droplet concentration into WRF-Chem to better constrain aerosol properties below the clouds. WRF-Chem has also been used to provide the first model-based regional quantification over the SEP of the aerosol indirect effects on climate (Q. and to describe a freetropospheric transport pathway for aerosol transport to the remote SEP (George et al 2013).…”
Section: Modeling Regional and Global Dynamical Modelsmentioning
confidence: 99%